Response of Hybrid Rice (Oryza sativa L.) to Varying Levels of Nitrogen and Homo-Brassinosteroids in Lateritic Zone of West Bengal - Bera, A. K.; Pramanik, K. (International Journal of Bio-resource and Stress Management, 2012)
A field experiment on hybrid rice (PHB-71) was conducted during kharif season of 2009 and 2010 in agriculture farm, Institute of Agriculture, Sriniketan, Visva-Bharati, West Bengal to study the effect of nitrogen and homo-brassinosteroids on growth, yield parameters and yield of hybrid rice (Oryza sativa L.) in lateritic zone of West Bengal in India. The experiment was conducted with five nitrogen levels, viz. 0, 50, 100, 150 and 200 kg ha-1 and three levels of homo-brassinosteroids (no spray, spary at panicle initiation stage and spray at panicle initiation+flowering stage). Application of nitrogen @ 150 kg ha-1 recorded significantly more panicle weight, grain yield (54.11 q ha-1) and harvest index (43.58%) whereas 200 kg ha-1 showed maximum plant height, number of tillers hill-1, number of effective tillers hill-1 and straw yield. In case of homo-brassinosteroids, spraying at PI+flowering stage resulted in significantly taller plants with more number of effective tillers hill-1, panicle weight, grain yield (47.29 q ha-1), straw yield (63.17 q ha-1 ) and harvest index (42.38%).